Effects of mental practice strategies associated to physiotherapy on gait and risk of falls in Parkinson's disease: a pilot study of a randomized clinical trial. (24th June 2020) - Silva, T; Silva, L; Silva, K; Silva, S; Silva, D; Lins, C; Coriolano, M
Abstract: Introduction Parkinson's Disease (PD) is a degenerative disorder that interferes with the voluntary movements due to dysfunction of the basal ganglia and presenting with motor signals, such as the reduction of gait speed. This contributes to an increased risk of falls. In rehabilitation, mental practice (MP) has been shown to promote plastic modulation of neural circuits and improve motor learning, but the results of research with MP in PD are still ambiguous due to the diversity of intervention strategies. Objectives To compare the effects of MP strategies associated to physiotherapy in gait and risk of falls in PD patients. Methodology We performed a pilot study of a clinical randomized, single blind, trial, conducted in accordance with the consort checklist. Patients with idiopathic PD were included and allocated to four groups: Control group (CG); Group with mental practice guided by images (MPI); Group with mental practice guided by audio (MPA); group with mental practice without a guide (MPWG). The subjects of the experimental groups were submitted to 15 sessions of physiotherapy and mental practice, while the CG received only physiotherapy. The sessions were held 2 times per week, 40 minutes for physiotherapy and approximately 5-10 minutes for the corresponding mental practice protocol. Spatial-temporal parameters of gait were assessed with the 10 meters Walking Test (TC10m), and the risk of falls was evaluated with the Timed Up and Go (TUG) test. Results The MPI group showed significant results for the parameters time (p = 0.027) and speed (p = 0.025) when compared with the results of the CG. No main effects for the group were observed concerning cadence and risk of falls had. Groups MPWG and MPA showed no significant results for the TC10m and TUG when compared with the CG. Conclusion The results of this pilot study suggest that MP guided by images associated to physical therapy was more effective to increase the gait speed than the alternative strategies.